Simulation of Baroclinic Current Pattern in Eastern Indonesian Region using Three-Dimensional Model - Syamsul Rizal; Ichsan Setiawan; Muhammad Muhammad; Taufiq Iskandar; Mulyadi Abdul Wahid (Jurnal Matematika & Sains, 2009)
In this investigation, the currents in Eastern Indonesian region are simulated by using the equations of motion (Navier-Stokes Equation). These equations are solved by the Hamburg Shelf Ocean Model (HAMSOM). Two cases are carried out, i.e. in the condition of west monsoon (February 1994) and east monsoon (August 1994). The simulation results are discussed for surface current, currents at 100-200 m, and the bottom current. In general, the results obtained agrees well with the work of Wyrtki, 1961 and Ahmat et al., 1995, but less with the work of Gordon and McClean, 1999.